Current and Projected Characteristics and Unique Health Care Needs of the Patient Population Served by the Department of Veterans Affairs - Health, RAND (RAND Corporation, 2015)
Veterans who rely on Department of Veterans Affairs (VA) health care are older and less healthy than veterans who do not, and the prevalence of health conditions in this population will increase. Not all eligible veterans use VA health care, and demand depends on such factors as access to other sources of health care. Analysis of a range of data sources provided insight into how the veteran population and demand for VA health care will change.